Community perspectives on anti-helminthiasis mass drug administration for school-age children in Ghana - Barry, Lansana; Andah, Nathaniel Larbi; Sidibé, Sidikiba; Delamou, Alexandre; Dako-Gyeke, Phyllis (Frontiers in Tropical Diseases, 2025)
BackgroundSoil-transmitted helminthiasis (STH) infections are neglected tropical diseases that affect populations worldwide, especially in low- and middle-income countries. Groups at risk include pre-school and school-age children as well as women of reproductive age. The World Health Organization (WHO) recommends mass drug administration (MDA) to control STH transmission in all endemic countries. This study explored community perspectives on STH anti-helminthiasis MDA.MethodsA phenomenological study using qualitative research methods was conducted. In-depth interviews with 15 caregivers, 5 community drug distributors (CDDs), and 3 key informants were conducted in Sekyere Central District, Ashanti Region, Ghana. Interviews were recorded, transcribed, and coded using NVivo software Version 12 (QSR International Pty Ltd., Cardigan, UK), applying both inductive and deductive approaches. Thematic analysis was then performed.ResultsAlthough some participants demonstrated good knowledge of STH, others attributed its causes to sugary foods. Participants also expressed confidence in traditional treatments, such as the use of herbs and leaves. In contrast, some viewed WHO-recommended medications such as albendazole and mebendazole as harmful. Major barriers to the Mass Drug Administration (MDA) program included limited information about the campaign, low awareness of the benefits of the medications, and insufficient motivation for Community Drug Distributors (CDDs).ConclusionNTD programmes should strengthen community education on the benefits of MDA to address gaps in community perspectives and knowledge related to STH and anti-helminthiasis interventions.